Examining trait self-control and communication patterns in romantic couples using the actor-partner interaction model. (1st February 2017) - Bornstein, Jerica X.; vanDellen, Michelle R.; Shaffer, Anne
Abstract: High self-control is associated with positive relationship outcomes. The purpose of this research was to examine the relationship between self-control and communication patterns between romantic partners. Dyadic data analyses revealed main effects of actor and partner self-control on mutually constructive communication and demand/withdraw. Additionally, an interaction between actor and partner self-control was related to mutual avoidance. These findings suggest self-control may be related to better communication abilities within relationships, providing one potential explanation for the association of self-control with better relationship outcomes. Highlights: Actor self-control (SC) positively predicted mutually constructive communication. Actor SC negatively predicted mutual avoidance and demand/withdraw (DW). High partner SC predicted actor report of mutually constructive communication. High partner SC predicted actor report of avoidance and DW communication.